Nothing Special   »   [go: up one dir, main page]

Week 2.3E Complex Functions (1)

Download as pdf or txt
Download as pdf or txt
You are on page 1of 9

2.

3 Complex Functions
Textbook: Section 17.6 – 17.7 (Zill)

Complex Exponential Function


The famous Euler’s formula define

eiθ = cos θ + i sin θ vir θ ∈ R

With this notation, together with our previous theory, we have

eiα eiβ = (cos α + i sin α) · (cos β + i sin β) = cos(α + β) + i sin(α + β) = ei(α+β)

which reminds us of the (real) exponential law, and thus can serve as a motivation for why eiθ is
defined as such.
This can be expanded to the following definition.

Definition 2.3.1 (Complex Exponential Function). For a complex number z = a + bi, we


define
ea+bi = ea (cos b + i sin b)

Similarly as in the real case, the following exponential laws are valid:

Theorem 2.3.2. For any z, w ∈ C, we have


ez
ez ew = ez+w and = ez−w
ew

Proof: Suppose z = a + bi and w = c + di where a, b, c, d ∈ R


Then, with the help of what we observed before the definition,

ez ew = ea+bi ec+di = ea ebi ec edi = ea ec ebi edi = ea+c e(b+d)i = ea+c+(b+d)i = ez+w

Further, notice that from the definition of complex division,


1 1 cos d − i sin d
= = = cos(−d) + sin(−d) = e−di
e di cos d + i sin d cos2 d + sin2 d
And thus
ez ez
= = ez e−c e−di = ez e−w = ez+(−w) = ez−w
ew ec edi

Example 2.3.3. Write ez in standard form a + ib in the following cases


3πi πi
(a) z = −2 + 4 (b) z = ln 5 − 2i (c) z = 10 − 3 ln π + 2

1
Solution:
 
3πi
z
(a) e = exp −2 + (b) ez = eln 5 e−2i
4 
     = 5 cos(−2) + i sin(−2)
3π 3π
= e−2 cos + i sin = 5 cos(2) − 5 sin(2)i
4 4
1 1
=− √ + √ i
2
e 2 e 2 2
  
z πi −3
 πi
(c) e = exp 10 − 3 ln π + = exp 10 + ln π exp
2 2
e 10   π   π  e 10  e 10
= 3 cos + i sin = 3 0 + i(1) = 3 i
π 2 2 π π

Example 2.3.4. Write f (z) = e2z = exp 2z in standard form.




Solution: Set z = x + iy ∈ C. Then

f (z) = e2z = e2(x−iy)


= e2x+i(−2y)
= e2x cos(−2y) + i sin(−2y)


=⇒ u = e2x cos(2y)
v = e2x sin(−2y) = −e2x sin(2y)

Theorem 2.3.5. The complex exponential function ez is periodic with period 2πi. That is

ez+2πi = ez vir alle z∈C

In particular, e2πi = 1

Proof:

ez+2πi = ez e2πi = ez cos(2π) + i sin(2π) = ez (1 + 0i)) = ez




Remark 2.3.6. If r is the modulus of z and θ an argument of z, we could alternatively write


the polar form as

z = r(cos θ + i sin θ) = reiθ or z = |z|ei arg(z)

√ 10
−1 + 3 i
Example 2.3.7. Write z = in the form a + ib.
(1 − i)14

Solution: Set z1 = −1 + 3i and z2 = 1 − i. Their polar representations are

2
√ y y
−1 + 3i

2π x
3 − π4
x 1−i

|z1 | = 2 |z2 | = 2

arg(z1 ) = 3 = arg (z2 ) = − π4 arg(z2 ) = − π4
Thus
10
210 exp 2π 210 exp 20πi

z110 3 i 3 
z = 14 = √ 14 14 = 7
z2 2 exp − π4 i 2 exp − 7πi 2
3 2π π π
since ez+10πi = ez
 
= 2 exp 6πi + 3 i + 4πi − 2 i = 8 exp 6 i
√ √
= 8 cos π6 + i sin π6 = 8 2 3 + 82 i = 4 3 + 4i
 

Complex Logarithmic Function


Just like in the real case, we would like to define the logarithmic function as an inverse of the
exponential function. But since ez = ez+2πi , there will not exist an inverse “function”. We will
rather define ln z as the collection of all solutions of ew = z.
We have, where loge is the real natural logarithm,

ew = z = |z|earg(z)i = eloge |z|+arg(z)i



⇐⇒ w = loge |z| + arg(z) + 2πn i, n∈Z

Notice that ew = 0 has no solutions, and thus ln z is undefined for z = 0.

Definition 2.3.8 (Complex Logarithm). For a non-zero complex number z, we define



ln z = loge |z| + i arg(z) + 2πn vir n ∈ Z

If we use the principal argument Arg(z) instead of the general argument arg(z), we will get a
function.

Definition 2.3.9. For a non-zero complex number z, the principal value of ln z is

Ln z = loge |z| + i Arg(z) waar − π < Arg(z) < π

Notice that

eln z = z but ln ez = z + 2πn i, n∈Z

Example 2.3.10. Determine ln(z) as well as the principal values Ln(z) in the following cases.
(a) z = −e3 (b) z = −i (c) z = −1 − i

3
Solution:
(a) z = −e3 (b) z = −i
3

θ = arg −e =π
θ = − π2 3π

of 2
−e 3 0
ln(z) = loge |z| + i arg(z) −i

= loge e3 + i(π + 2nπ), n∈Z ln(z) = loge | − i| + i arg(−i)


= loge (1) + i 3π

= 3 + iπ(1 + 2n), n∈Z 2 + 2πn , n ∈ Z
= iπ 32 + 2n , n ∈ Z

Ln(z) = 3 + i Arg −e3


Ln(z) = i − π2 = − π2 i

= 3 + iπ

(c) z = −1 − i

π
θ=π+ 4
−1

−1

√ 
5π 1 5
 
ln(z) = loge 2 +i 4 + 2πn = 2 loge (2) + iπ 4 + 2n , n∈Z

1 π 1 3π

Ln(z) = 2 loge (2) + i −π + 4 = 2 loge (2) − 4 i

Example 2.3.11. Solve the following complex equation.



e1+2z = 1 − 3 i

Solution: Notice that an argument of 1 − 3 is − π3 , and that 2 is its modulus. Now take the
complex logarithm on both sides.
 √ 
ln e1+2z = ln 1 − 3 i


√  √ 
=⇒ 1 + 2z = loge 1 − 3i + i arg 1 − 3 i
= loge (2) + i − π3 + 2πn

n∈Z
π

=⇒ 2z = −1 + loge (2) + i − 3 + 2nπ n∈Z
1 1 π

=⇒ z = − 2 + 2 loge (2) + i − 6 + nπ n∈Z

Notice that this equation has infinitely many solutions.

Similarly, as in the real case, the following properties are valid for the complex case.

4
Theorem 2.3.12. For any two non-zero complex numbers z and w, we have
z
ln(zw) = ln z + ln w and ln = ln z − ln w
w

Example 2.3.13. Let z1 = i and z2 = −1 + i


(a) Confirm that ln (z1 z2 ) = ln (z1 ) + ln (z2 )
(b) Is Ln (z1 z2 ) = Ln (z1 ) + Ln (z2 ) ?

Solution: We have
√ √ √
|z1 | = 1 |z2 | = 2 |z3 | = 1 · 2= 2
π 3π π 3π 5π
arg(z1 ) =2 arg(z2 ) = 4 arg(z3 ) = 2 + 4 = 4
Arg(z1 ) = π2 Arg(z2 ) = 3π
4 Arg(z1 z2 ) = − 3π
4

Thus

ln(z1 ) + ln(z2 ) = loge 1 + i π2 + 2πn1 + loge 2 + i 3π
 
4 + 2πn2 , n1 , n2 ∈ Z
√ 5π
 √ 5π

= loge 2 + i 4 + 2π(n1 + n2 ) = loge 2 + i 4 + 2π(n) , n ∈ Z

= log(z1 z2 )
But
√ √
Ln(z1 ) + Ln(z2 ) = loge 1 + π2 i + loge 3 + 3π 4 i = loge 3 +

4 i

Ln(z1 z2 ) = loge 2 − 3π 4 i ̸= Ln(z1 ) + Ln(z2 )
Thus, Ln(z1 z2 ) ̸= Ln(z1 ) + Ln(z2 ) in this case.

Example 2.3.14. Solve the following complex equation.


e2z + 2ez + 2 = 0

Solution: This equation is a quadratic equation in terms of ez . Thus



z 2 z z −2 ± −4
(e ) + 2e + 2 = 0 =⇒ e = = −1 ± i
2
=⇒ ez = −1 + i or ez = −1 − i
=⇒ z = ln(−1 + i) or z = ln(−1 − i)
Notice that

| − 1 + i| = 2 = | − 1 − i| arg(−1 − i) = − 3π
4 arg(−1 + i) = 3π
4
Thus

2 + i 3π

ln(−1 + i) = loge 4 + 2πn 1 n1 ∈ Z

ln(−1 − i) = loge 2 + i − 3π

4 + 2πn2 n2 ∈ Z
which are then all solutions of this equation.

5
Complex Trigonometric Functions
For x ∈ R, from Euler’s Formula it follows
eix = cos x + i sin x and e−ix = cos x − i sin x
that
1
eix + e−ix 1
eix − e−ix
 
cos x = 2 and sin x = 2i
We now define the complex trigonometric functions by replacing the real number x in the above
formula with the complex number z.

Definition 2.3.15. For any z ∈ C, we define

cos z = 12 eiz + e−iz 1


eiz − e−iz
 
and sin z = 2i

We define the other four trigonometric functions as usual, in terms of cos z and sin z:
sin z 1 1 cos z
tan z = sec z = cosec z = cot z =
cos z cos z sin z sin z

Similarly as in the real case, the following are also valid


Theorem 2.3.16. For any complex numbers z, w ∈ C, we have
ˆ sin(−z) = − sin z and cos(−z) = cos z
ˆ cos2 z + sin2 z = 1
ˆ sin (z1 ± z2 ) = sin z1 cos z2 ± cos z1 sin z2
ˆ cos (z1 ± z2 ) = cos z1 cos z2 ∓ sin z1 sin z2
ˆ sin(2z) = 2 sin z cos z and cos(2z) = cos2 z − sin2 z
Which is also useful for computations, is the following result.

Theorem 2.3.17. For any complex number a + bi,


ˆ sin(a + bi) = sin(a) cosh b + i cos(a) sinh b
ˆ cos(a + bi) = cos(a) cosh b − i sin(a) sinh b

Proof: We prove the second point. The proof of the first point is similarly.

6
According to the definitions, we have

cos(a + bi) = 21 ei(a+bi) + 21 e−i(a+bi) = 21 eai−b + 21 e−ai+b


= 12 e−b (cos a + i sin a) + 12 eb cos(−a) + i sin(−a)


= 21 e−b cos a + i 12 e−b sin a + 12 eb cos a − i 12 eb sin a


   
= cos(a) 12 eb + e−b − i sin(a) 21 eb − e−b
= cos(a) cosh b − i sin(a) sinh b

Example 2.3.18. Write the following in the form of a + ib




(a) cos(π + i ln 2) (b) tan(−i ln 3) (c) sin 4 − 2i

Solution:
(a) cos(π + i ln 2) = cos(π) cosh(ln 2) − i sin(π) sinh(ln 2)
eln 2 + e− ln 2
− i · 0 = − 12 2 + 21 = − 54

= −1 ·
2

sin 0 + i(− ln 3)
(b) tan(−i ln 3) = 
cos 0 + i(− ln 3)
sin(0) cosh(− ln 3) + i cos(0) sinh(− ln 3)
=
cos(0) cosh(− ln 3) − i sin(0) sinh(− ln 3)
i − ln 3 − eln 3 i 13 − 3
 
i sinh(− ln 3) 2 e 8
= = 1 − ln 3 ln 3
= 1 = − 10 i = − 45 i
cosh(− ln 3) 2 (e +e ) 3 +3

(c) sin 3π 3π 3π
  
4 − 2i = sin 4 cosh(−2) + i cos 4 sinh(−2)
 
= √12 · 12 e−2 + e2 + i − √12 12 e−2 − e2
 
√ √
= 42 e−2 + e2 + i 42 e2 − e−2
 

Example 2.3.19. Determine all complex numbers z such that

cos z = i

Solution: Method 1: Definition


From the definition it follows that

cos z = 12 eiz + e−iz = i eiz + e−iz = 2i



=⇒
2 2
=⇒ eiz + e−iz · eiz = 2ieiz =⇒ eiz − 2ieiz + 1 = 0

7
With the quadratic formula, we have

√ √ 
p
iz 2i ± (−2i)2 − 4 2i ± −4 − 4 
e = = = i ± 2i = 1 ± 2 i
2(1) 2
 √    √  
=⇒ iz = ln 1 + 2 i or iz = ln 1 − 2 i
 √    √  
=⇒ z = −i ln 1 + 2 i or z = −i ln 1 − 2 i
 √ 
z = −i loge 1 + 2 + π2 + 2πn

=⇒
√ 
2 − 1 + − π2 + 2πn

or z = −i loge for n ∈ Z

Method 2: Identity
Suppose z = a + bi. Then
i = cos(a + bi) = cos(a) cosh b − i sin(a) sinh(b)
=⇒ cos(a) cosh(b) = 0 and sin(a) sinh(b) = −1
Since cosh(b) is always positive, we must have
π
cos(a) = 0 =⇒ a= 2 + πn n∈Z
Notice that
π π
 
sin 2 + π(2k) = +1 and sin 2 + π(2k + 1) = −1 k∈Z
So if n is even, then
 
−1 = sinh(b) = 1
2 eb − e−b
=⇒ 0 = e2b + 2eb − 1

b −2 ± 4 + 4 √ √
=⇒ e = = −1 ± 2 = −1 + 2 since eb > 0
2 √ 
=⇒ b = loge −1 + 2

And if n is odd, then


   √ 
1 = sinh(b) = 1
2 eb − e−b =⇒ ... =⇒ b = loge 1 + 2

Consequently, the solutions are


√ 
π

z = a + bi = 2 + 2πk + i loge 2−1
π
  √ 
or z = a + bi = 2 + π(2k + 1) + i loge 1 + 2 k∈Z

Example 2.3.20. Determine all z ∈ C for which


sin z = i sinh(2)
using the definition of equality of complex numbers.

8
Solution: Let z = a + bi, where a, b ∈ R. Then

i sinh(2) = sin(a + bi) = sin(a) cosh(b) + i cos(a) sinh(b)


=⇒ sin(a) cosh(b) = 0 and cos(a) sinh(b) = sinh(2)

Since cosh(b) > 0 for all real numbers b, we have

sin(a) = 0 =⇒ a = nπ n∈Z

Notice that

cos(πn) = (−1)n

We thus consider two cases. If n = 2k is even, then

sinh(2) = cos(a) sinh(b) = =⇒ 2=b

since sinh is an injective function (consider its graph!). And if n = 2k + 1 is odd, then we have

sin(2) = cos(a) sinh(b) = − sinh(b) = sinh(−b) =⇒ 2 = −b

Thus, the solutions are

z = 2kπ − 2i or z = (2k + 1)π + 2i, k∈Z

You might also like